Use of bilateral prophylactic nipple‐sparing mastectomy in patients with high risk of breast cancer. Issue 10 (20th May 2020) - Valero, M. G.; Moo, T.‐A.; Muhsen, S.; Zabor, E. C.; Stempel, M.; Pusic, A.; Gemignani, M. L.; Morrow, M.; Sacchini, V.
Abstract : Background: Nipple‐sparing mastectomy (NSM) is being performed increasingly for risk reduction in high‐risk groups. There are limited data regarding complications and oncological outcomes in women undergoing bilateral prophylactic NSM. This study reviewed institutional experience with prophylactic NSM, and examined the indications, rates of postoperative complications, incidence of occult malignant disease and subsequent breast cancer diagnosis. Methods: Women who had bilateral prophylactic NSM between 2000 and 2016 were identified from a prospectively maintained database. Rates of postoperative complications, incidental breast cancer, recurrence and overall survival were evaluated. Results: A total of 192 women underwent 384 prophylactic NSMs. Indications included BRCA1 or BRCA2 mutations in 117 patients (60·9 per cent), family history of breast cancer in 35 (18·2 per cent), lobular carcinoma in situ in 29 (15·1 per cent) and other reasons in 11 (5·7 per cent). Immediate breast reconstruction was performed in 191 patients. Of 384 NSMs, 116 breasts (30·2 per cent) had some evidence of skin necrosis at follow‐up, which resolved spontaneously in most; only 24 breasts (6·3 per cent) required debridement. Overall, there was at least one complication in 129 breasts (33·6 per cent); 3·6 and 1·6 per cent had incidental findings of ductal carcinoma in situ and invasive breast cancer respectively. The nipple – areola complex was preserved entirely in 378 mastectomies. After a median follow‐up of 36·8 months, there had been no deaths and no new breast cancer diagnoses. Conclusion: These findings support the use of prophylactic NSM in high‐risk patients. The nipples could be preserved in the majority of patients, postoperative complication rates were low, and, with limited follow‐up, there were no new breast cancers. Abstract : This study reviewed an institutional experience with prophylactic nipple‐sparing mastectomy, and examined the indications, rates of postoperative complications, incidence of occult malignant disease and subsequent breast cancer diagnosis. This institutional experience supports the use of prophylactic nipple‐sparing mastectomy in high‐risk patients. Safe option Abstract : Antecedentes: La mastectomía con preservación del pezón ( nipple‐sparing mastectomy, NSM) se realiza cada vez más para reducir riesgos en los grupos de pacientes de alto riesgo. Se dispone de pocos datos sobre complicaciones y resultados oncológicos en mujeres sometidas a NSM bilateral profiláctica. Este estudio revisó la experiencia institucional de la NSM profiláctica, y analizó las indicaciones, tasas de complicaciones postoperatorias, incidencia de enfermedad maligna oculta y diagnóstico de subsiguiente cáncer de mama. Métodos: Se identificaron mujeres sometidas a NSM bilateral profiláctica durante el periodo 2000‐2016 a partir de una base de datos prospectiva. Se evaluaron tasas de complicaciones postoperatorias, cáncer de mama incidental, recidiva y supervivencia global. Resultados: Un total de 192 mujeres fueron sometidas a 384 NSMs profilácticas. Las indicaciones incluyeron mutaciones BRCA1 o BRCA2 en 117 (61%) pacientes, historia familiar de cáncer de mama en 35 (18%), carcinoma lobulillar in situ en 29 (15%) y otros motivos en 11 (5, 7%). La reconstrucción mamaria inmediata se realizó en 191 pacientes. De las 384 NSMs, 116 (30%) presentaron alguna evidencia de necrosis de la piel durante el seguimiento y la mayoría se resolvieron de forma espontánea, con solo 24 (6, 2%) mamas que requirieron desbridamiento. Globalmente hubo al menos una complicación en 129 (34%) mamas; 3, 6% y 1, 6% tuvieron hallazgos incidentales de carcinoma ductal in situ o cáncer de mama invasivo, respectivamente. El complejo areola‐pezón se preservó completamente en 378 mastectomías. Tras una mediana de seguimiento de 36, 8 meses, no hubo fallecimientos ni ningún diagnóstico nuevo de cáncer de mama. Conclusión: Estos hallazgos apoyan la utilización de la NSM profiláctica en pacientes de alto riesgo. En la mayoría pacientes fue posible la preservación del pezón, las tasas de complicaciones postoperatorias fueron bajas y, con un seguimiento limitado, no hubo nuevos casos de cáncer de mama.